Criminal Policy Against The Criminal Action Of Subsidized Fuel Hooking In Bongo Zero Village - Rizki Hidayat Palantu (Universitas Negeri Gorontalo, 2020)
The criminal policy against the criminal act of misuse of fuel oil and natural gas that occurred in the Bongo Nol gas station area was more focused on the